Debunking the Non-Fungibility of NFTs - Proaño Alcívar, David (USFQ Law Review, 2024)
Non-Fungible Tokens or NTFs are digital files representing a particular value, such as an image, an asset, or a property title. As implied by their name, these goods have commonly been given the character of being non-fungible things because each one of them is unique and cannot be replicated. However, said qualification is a mistake since the fungibility of an asset is relative to the obligation in which it is immersed and does not correspond to a natural characteristic that an object may always have automatically or with the fact of non-repeatability or inability to be replicated. For this reason, NFTs can be fungible depending on the features that arise from the legal obligation, which may or may not include the specific NFT’s identification code as a requirement.